2014
DOI: 10.1186/1532-429x-16-19
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative three-dimensional cardiovascular magnetic resonance myocardial perfusion imaging in systole and diastole

Abstract: BackgroundTwo-dimensional (2D) perfusion cardiovascular magnetic resonance (CMR) remains limited by a lack of complete myocardial coverage. Three-dimensional (3D) perfusion CMR addresses this limitation and has recently been shown to be clinically feasible. However, the feasibility and potential clinical utility of quantitative 3D perfusion measurements, as already shown with 2D-perfusion CMR and positron emission tomography, has yet to be evaluated. The influence of systolic or diastolic acquisition on myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 34 publications
(59 reference statements)
1
45
0
Order By: Relevance
“…Recent advances reported in the journal have included improved flow mapping, [13] real-time imaging, [4] T1 mapping, [57] simulations, [8, 9] perfusion, [1012] coronary imaging, [13] diffusion tensor imaging, [1416] feature tracking, [1720] and strain assessment. [21, 22] The full breadth of new developments is described in the papers in the section.…”
Section: Technical Developmentsmentioning
confidence: 99%
“…Recent advances reported in the journal have included improved flow mapping, [13] real-time imaging, [4] T1 mapping, [57] simulations, [8, 9] perfusion, [1012] coronary imaging, [13] diffusion tensor imaging, [1416] feature tracking, [1720] and strain assessment. [21, 22] The full breadth of new developments is described in the papers in the section.…”
Section: Technical Developmentsmentioning
confidence: 99%
“…29 By using electrocardiogram-triggered MRI acquisitions, a time resolution of three to six slices per cardiac cycle can be achieved with reasonable signal-to-noise ratio, also surpassing the temporal capabilities of PET imaging. However, one of the most important goals in recent research on cardiac perfusion MRI is to increase the spatial coverage of the heart muscle using either three-dimensional sequences or accelerated multislice approaches, which despite recent advances 30,31 is still lagging behind the whole heart coverage of PET. With the advent of integrated PET/MRI systems, equivalent coverage of the myocardium with PET and MRI perfusion imaging becomes highly desirable when comparing results between modalities or developing complementary imaging schemes.…”
Section: Mpi T1 Mapping and Extracellular Volume Quantificationmentioning
confidence: 99%
“…However, measuring perfusion at end systole further limits the acquisition window to 150 ms or less to avoid cardiac motion artifacts . Both the Motwani et al (192 ms acquisition window) and the Manka et al (200 ms acquisition window) studies exceed that suggested limit …”
Section: Introductionmentioning
confidence: 99%
“…Resting myocardial perfusion can identify microvascular obstruction, but myocardial perfusion reserve (MPR) is a more sensitive measurement of microvascular function and a strong surrogate marker for ischemia . The increased complexity of using a vasodilator agent and the shorter acquisition window associated with stress perfusion have limited the measurement of MPR using 3D cardiac perfusion to only a few reported studies . In addition, even though MR estimates of perfusion at systole and diastole have shown similar diagnostic accuracy, most sources agree that imaging at end systole is preferable due to the increased myocardium wall thickness .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation